Low stability of the reduced state of Mycobacterium tuberculosis NrdH redoxin. Issue 3 (2nd February 2016) - Liu, Ya‐Jun; Song, Xiaxia; Li, Yifei; Xuan, Jinsong; Cui, Qiu; Wang, Jinfeng; Feng, Yingang
Abstract : NrdH redoxin is the only hydrogen donor for ribonucleotide reductase in Mycobacterium tuberculosis . Several crystal structures of NrdH redoxins in the oxidized state from different species have been reported, but no structure of the reduced state has yet been reported. Using NMR spectroscopy, we found surprisingly that the reduced NrdH redoxin from M. tuberculosis is largely unfolded at a pH lower than the p K a of its first active site cysteine, and the structural basis of the low stability was analyzed. In addition, a single mutant of the NrdH redoxin suitable to determine the structure in the reduced state was obtained. Abstract :